Interactions Between a Belowground Herbivore and Primary and Secondary Root Metabolites in Wild Cabbage - Van Geem, Moniek (J Chem Ecol, 2015)
Plants are attacked by both above- and belowground herbivores. Toxic secondary compounds are part of the chemical defense arsenal of plants against a range of antagonists, and are subject to genetic variation. Plants also produce primary metabolites (amino acids, nutrients, sugars) that function as essential compounds for growth and survival. Wild cabbage populations growing on the Dorset coast of the UK exhibit genetically different chemical defense profiles, even though they are located within a few kilometers of each other. As in other Brassicaceae, the defensive chemicals in wild cabbages constitute, among others, secondary metabolites called glucosinolates. Here, we used five Dorset populations of wild cabbage to study the effect of belowground herbivory by the cabbage root fly on primary and secondary chemistry, and whether differences in chemistry affected the performance of the belowground herbivore. There were significant differences in total root concentrations and chemical profiles of glucosinolates, amino acids, and sugars among the five wild cabbage populations. Glucosinolate concentrations not only differed among the populations, but also were affected by root fly herbivory. Amino acid and sugar concentrations also differed among the populations, but were not affected by root fly herbivory. Overall, population-related differences in plant chemistry were more pronounced for the glucosinolates than for amino acids and sugars. The performance of the root herbivore did not differ among the populations tested. Survival of the root fly was low (<40 %), suggesting that other belowground factors may override potential differences in effects related to primary and secondary chemistry. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10886-015-0605-7) contains supplementary material, which is available to authorized users.